Cancer incidence in urban bus drivers and tramway employees: a retrospective cohort study. Issue 9 (September 1998) - Soll-Johanning, H; Bach, E; Olsen, J H; Tüchsen, F
Abstract : OBJECTIVE: To investigate the risk of cancer associated with exposure to air pollution among bus drivers and tramway employees. METHODS: A retrospective cohort study of 18, 174 bus drivers or tramway employees in Copenhagen in the period 1900-94. Data on employment were obtained from company files. Information on cancer was obtained from the Danish Cancer Registry. RESULTS: Findings showed that bus drivers or tramway employees had an increased risk of all malignant neoplasms (standardised incidence ratio (SIR) 1.24, 95% confidence interval (95% CI) 1.19 to 1.30). The relative risk was significantly increased for both men and women (SIR 1.24, 95% CI 1.19 to 1.30 and 1.28, 1.06 to 1.53, respectively). People employed for < 3 months had no increased risk of cancer (1.04, 0.81 to 1.31). For men who were employed for > 3 months the risk of lung cancer (1.6, 1.5 to 1.8), laryngeal cancer (1.4, 1.0 to 1.9), kidney cancer (1.6, 1.3 to 2.0), bladder cancer (1.4, 1.2 to 1.6), skin cancer (1.1, 1.0 to 1.2), pharyngeal cancer (1.9, 1.2 to 2.8), rectal cancer (1.2, 1.0 to 1.5) and liver cancer (1.6, 1.2 to 2.2) was significantly increased. For women employed for > 3 months the risk of lung cancer was significantly increased (2.6, 1.5 to 4.3). CONCLUSION: This cohort study shows that bus drivers and tramway employees are at an increased risk of developing several types of cancer. This might be due to the exposure to air pollution during working hours or to other risk factors, primarily smoking.